1975
DOI: 10.1021/ed052p350
|View full text |Cite
|
Sign up to set email alerts
|

The Apollo missions and the chemistry of the moon

Abstract: The Apollo Missions and the Chemistry of the MoonThe purpose of this paper is to present a picture of the principal chemical features of the Moon, in light of the several Apollo missions. General physical features of the Moon will also be discussed briefly. Finally, several theories of the origin of the Moon will be considered, particularly those presented at the Fifth Lunar Science Conference. General Features of the Lunar LandscapeFrom Earth, the most evident feature of the Moon is its division into brig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1976
1976
2003
2003

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The flight of Apollo 15 resulted in the discovery of a sample of crystalline rock that was 4.5 billion years old (1,15,16). Why send humans when robots may be able to do what astronauts were doing at less cost and without the risk to life?…”
Section: The Educated Observermentioning
confidence: 99%
See 3 more Smart Citations
“…The flight of Apollo 15 resulted in the discovery of a sample of crystalline rock that was 4.5 billion years old (1,15,16). Why send humans when robots may be able to do what astronauts were doing at less cost and without the risk to life?…”
Section: The Educated Observermentioning
confidence: 99%
“…In fact, some samples that appear gray on the macroscopic level have other colors such as green when viewed on the microscopic level (1,19). Astronaut James Lovell first described the moon as gray with no other color during the flight of Apollo 8.…”
Section: The Educated Observermentioning
confidence: 99%
See 2 more Smart Citations
“…We found that an excellent technique for generating discussion on this topic was to have students imagine that they were astronauts who want to analyze the lunar surface. An excellent article by Pacer and Ehmann has appeared recently in this Journal discussing the chemical features of the moon (5).…”
Section: Organizationmentioning
confidence: 99%